Morphometry And Morphotectonic Characteristics Of The Cisokan Watershed Segments Cilengkong And Cisukarama, West Java, Indonesia - Saprana, Rifqi Dwi; Sophian, Irvan; Khoirullah, Nur; Ismawan, Ismawan (Journal of Geological Sciences and Applied Geology, 2021)
West Java has a complex geological structure characteristic due to subduction events in the south of Java Island. The control of the geological structure affects the formation of the surrounding landscape, so analysis is needed to assess its activities. The research was conducted in the Cisokan sub-watershed in the Cilengkong and Cisukarama segments in Cianjur and West Bandung districts, West Java. The purpose of this study was to determine the morphometric and morphotectonic characteristics of the Cisokan watershed in the Cilengkong and Cisukarama segments. The method used is studio analysis using applications to process digital image data into morphometric and morphotectonic analysis parameters. The parameters analyzed were the bifurcation ratio, drainage density, basin shape index, drainage basin asymmetry, and mountain front sinuosity. The results obtained are that the Cilengkong segment has an Rb value of 4 - 4.5 with a medium flow density, a BS value of 1.80, an AF value of 25.8, and an SMF value of 1.19 - 2.78. The Cisukarama 1 segment has an Rb value of 4 - 4.25, a BS value of 1.62, an AF value of 57.14, and an SMF value of 1.66 - 3.41. The Cisukarama 2 segment has a value of Rb 3 - 4.25, a BS value of 1.59, an AF value of 42.5, and an SMF value of 1.34 and 2.13. The conclusion obtained is that tectonic activity as a landscape-forming factor in the study area decreases or even stops.